Turnover Intention pada Gen Z: Peran Meaningful Work dan Work Engagement sebagai Mediator - violla dwi puspita; Rahmad Purnama; Ira Hidayati (Universitas Darul Ulum, 2026)
Generation Z is entering the workforce and tends to exhibit turnover intention. Meaningful work is considered as a predictor of turnover intention, however, there is still inconsistencies in the findings of previous research. Therefore, work engagement is considered as a mediator. This study aims to ascertain the role of work engagement as a mediator in the relationship between meaningful work and tunover intention among generation Z. This study was conducted on 130 generation Z employees (aged 18-27 years) with the method used is quantitative and data were analyzed using SEM-PLS with a second order factor model. The results indicate (1) meaningful work has a significant effect on work engagement. (2) work engagement has insignificant effect on turnover intention. (3) meaningful work has insignificant effect on turnover intention, and (4) work engagement does not have a role as a mediator between meaningful work and turnover intention